Influence the Graphene Filler Addition on the Tensile Behavior of Natural Kenaf Fiber-Based Hybrid Nanocomposites. (4th December 2022) - Natrayan, L.; Kaliappan, S.; Hatti, Gururaj; Patil, Pravin P.; Gaur, Piyush; Manikandan, T.; Murugan, P.
Abstract : In current centuries, emphasis has moved from previous resources and compounds to lightweight substances to generate softer, most effective components for particular needs. Using organic kenaf fibers with nanoreinforced epoxy polymers in a blended microbially nanocomposite can improve properties and be environmentally friendly. Adding graphene powder to the epoxy resin increases barrier and mechanical properties while maintaining rigidity without compromising toughness. To explore the impression of such parameters on the materials' properties of the construction, a mechanical test on nanocomposite features, such as size, filler content, and treatment effect, may be utilized. The elastic behavior, tension characteristics, and stress at vintage for three types of nanobased materials were calculated using the test results: graphite raw kenaf, nanosheets and sun-bleached kenaf fibers, salinized graphene oxide, and epoxy reinforced with salinized kenaf fibers. The impact of nanocomposite magnitude, filler concentration, and filler processing on mechanical properties is carefully investigated. According to the findings, the three-weight proportion of 75 nm-sized particles with salinized filler and kenaf fiber produces the maximum mechanical performance. Compared to other combinations, these combinations increase tensile strength by 16%. However, it appears to be beneficial when it comes to strength properties and deflection. Because of flaws and cavities at the micrometer level, the framework was less robust and distorted quickly after including a nanoparticle filler.